2003
DOI: 10.1289/ehp.5540
|View full text |Cite
|
Sign up to set email alerts
|

In ovo exposure to o,p -DDE affects sexual development but not sexual differentiation in Japanese medaka (Oryzias latipes).

Abstract: Despite being banned in many countries, dichlorodiphenyltrichloroethane (DDT) and its metabolites dichlorodiphenyldichloroethylene (DDE) and dichlorodiphenyldichloroethane (DDD) continue to be found in fish tissues at concentrations of concern. Like o,p -DDT, o,p -DDE is estrogenic and is believed to exert its effects through binding to the estrogen receptor. The limited toxicologic data for o,p -DDE suggest that it decreases fecundity and fertility of fishes. We conducted an egg injection study using the d-rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…Although the o,p 0 -isomers historically were considered relatively benign, recent studies have determined that o,p 0 -isomers are endocrine active. Dietary exposure to o,p 0 -DDT and o,p 0 -DDE can affect liver and gonad size, plasma vitellogenin concentrations, and lipid levels in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Papoulias et al, 2003). Ungerer and Thomas (1996) reported that concentrations of o,p 0 -DDT were positively correlated with gonadosomatic index in Atlantic croaker (Micropogonias undulatus).…”
Section: Childersburg Eureka Lavaca Mcintosh Bucksmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the o,p 0 -isomers historically were considered relatively benign, recent studies have determined that o,p 0 -isomers are endocrine active. Dietary exposure to o,p 0 -DDT and o,p 0 -DDE can affect liver and gonad size, plasma vitellogenin concentrations, and lipid levels in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Papoulias et al, 2003). Ungerer and Thomas (1996) reported that concentrations of o,p 0 -DDT were positively correlated with gonadosomatic index in Atlantic croaker (Micropogonias undulatus).…”
Section: Childersburg Eureka Lavaca Mcintosh Bucksmentioning
confidence: 99%
“…Dietary exposure to technical DDT has reduced survival in fish at multiple life stages (see review by Jarvinen and Ankley, 1999), and protective thresholds for whole-body total DDT concentrations have been recommended for early life stage, juvenile, and adult fish (Beckvar et al, 2005). In addition, exposure to p,p 0 -DDE, o,p 0 -DDT, and o,p 0 -DDE can affect behavior and disrupt the endocrine and immune systems in fish (Donohoe and Curtis, 1996;Ungerer and Thomas, 1996;Faulk et al, 1999;Milston et al, 2003;Papoulias et al, 2003;GarciaReyero et al, 2006;Barber et al, 2007). Exposure to p,p 0 -DDE has been associated with reduced reproductive success of bird populations; bald eagle (Haliaeetus leucocephalus) and osprey (Pandion haliaetus) are especially susceptible to eggshell thinning after exposure (Anderson and Hickey, 1972;Wiemeyer et al, 1984Wiemeyer et al, , 1988.…”
mentioning
confidence: 99%
“…Technical-grade DDT contains 65-80% p,p'-DDT, 15-21% o,p'-DDT and up to 4% p,p'-DDD (bis[4-chlorophenyl]-1,1,-dichloroethane) (ATSDR, 2002). The o,p-isomer constitutes about 15% of technical-grade DDT, and has been reported to be weakly estrogenic (Donohoe and Curtis, 1996;Metcalfe et al, 2000;Papoulias et al, 2003). DDTisomers, including o,p'-DDT have been implicated in reduced development of penises in male alligators from a contaminated Lake Apopka, Florida, USA (Guillete et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Gray et al (1999) reported that in Japanese medaka, the number of testisova in adult fish was lower than that in fry after exposure to octylphenol, suggesting that the stages of gonadal differentiation were optimal for the incidence of testis-ova by the exposure to estrogenic chemicals. On the other hand, Papoulias et al (2003) showed that ovo exposure to xeno-oestrogenic DDE did not affect the evidence of intersex gonads in Japanese medaka, Oryzias latipes (Temminck et Schlegel, 1846), although DDE can interact with hepatic estrogen binding sites and induce vitellogenesis in rainbow trout (Donohoe and Curtis 1996). Taking these results into the conclusion, pendimethalin affects the development of adult gonads in fish by acting as agonistic of estrogen, causing an intersex condition in some male gonads.…”
Section: Discussionmentioning
confidence: 98%